Effect of Zinc Supplementation on Heat Induced Gross Changes in Testes of Adult Mice (Medical Forum Monthly, 2020)
Objective: To compare the effects of Zinc supplementation on heat induced gross changes in testes of adult mice with placebo.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Anatomy Department ANMC Islamabad and Anatomy Department Sialkot Medical College, Sialkot in collaboration with (N.I.H) Islamabad from January 2016 to May 2017.Materials and Methods: Fifty-four adult male BALB/c mice were divided into two main groups. Control group of 18 mice and Experimental group of 36 mice. Control group was further divided into Normal control group of 9 mice and Experimental control group of 9 mice. Normal control group was given neither heat nor given any drug or placebo and were sacrificed on day 0 of the experiment. Experimental control group was given limited body heat and then sacrificed after 48 hours of heat exposure. Experimental group was further divided into two groups, Group C and Group D. Group C was further subdivided into C1, C2, C3.C1 was given limited body heat then placebo (Normal Saline) for 15 days, C2 for 30 days and C3 for 60 days. Group D was further subdivided into subgroups D1, D2, and D3. D1 was given limited body heat then ZnSO4 for 15 days, D2 for 30 days and D3 for 60 days. 6 mice from group C were sacrificed on 15, 30 and 60 days each. 6 mice from group D were sacrificed on 15, 30 and 60 days each. Testes were dissected out for gross examination.Results: Consistency was firm after heat exposure, weight was reduced but it regained after drug treatment.Conclusion: Zinc supplementation completely reverses the gross changes produced by limited heat in testes of adult mice.